2014
DOI: 10.1158/1535-7163.mct-13-0240
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Invulnerability of Cancer Stem Cells: Two-Step Strategy to Kill the Stem-like Cell Subpopulation of Multiple Myeloma

Abstract: In multiple myeloma, the presence of highly resistant cancer stem cells (CSC) that are responsible for tumor metastasis and relapse has been proven. Evidently, for achieving complete response, new therapeutic paradigms that effectively eradicate both, CSCs and bulk cancer populations, need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…However, a few studies have shown that some NM enzymes are functionally involved in de-differentiation processes, like the ectonucleotidase ENPP1 in the maintenance of the CSCs-like state in glioblastoma (Bageritz et al, 2014). Similarly, treatment with non-toxic doses of TS-inhibiting drugs was found sufficient to induce a differentiation in multiple myeloma CSCs and sensitize the cells for radiotherapy (Morgenroth et al, 2014). These observations, together with the first demonstration of a connection between TS and EMT (Siddiqui et al, 2017), prompted us to investigate the EMT-driven TNBC model (Mani et al, 2008;Taube et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies have shown that some NM enzymes are functionally involved in de-differentiation processes, like the ectonucleotidase ENPP1 in the maintenance of the CSCs-like state in glioblastoma (Bageritz et al, 2014). Similarly, treatment with non-toxic doses of TS-inhibiting drugs was found sufficient to induce a differentiation in multiple myeloma CSCs and sensitize the cells for radiotherapy (Morgenroth et al, 2014). These observations, together with the first demonstration of a connection between TS and EMT (Siddiqui et al, 2017), prompted us to investigate the EMT-driven TNBC model (Mani et al, 2008;Taube et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are, in fact, highly dependent on the de novo synthesis of nucleotides to produce sufficient DNA and RNA precursors to support their growth, and some cancer-promoting signaling pathways have been shown to regulate NM (Tong et al, 2009). However, a few recent studies have suggested that nucleotides-generating metabolic pathways may also serve as regulators of cancer stemness (Bageritz et al, 2014;Morgenroth et al, 2014), opening the possibility that some NM enzymes are implicated in cancer cell de-differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…These different effects account for the unique advantages of targeted nano-radiotherapy using Auger electron emitting drugs [23]. Recently, we presented a new promising approach involving radio-sensitization of myeloma stem-like cells by FdUrd pre-treatment followed by a DNA nano-irradiation by incorporated [I-125]ITdU [24]. FdUrd was shown to activate the relatively quiescent myeloma stem-like cells to enter cell cycling and to differentiate.…”
Section: Introductionmentioning
confidence: 99%
“…ALDH1A1 plays a major role in the metabolism of reactive aldehydes derived from ethanol. Because ALDH1A1 activity is increased in stem cell populations in multiple myeloma, acute myeloid leukemia, and brain and breast cancers [13][14][15][16][17], it may be a marker of malignant stem cell populations [18]. Because of its role in the metabolization of reactive acetaldehyde, ALDH1A1 is expressed at high levels in stem cells and regulates stem cell function [12].…”
mentioning
confidence: 99%